Development of Science Learning Devices Using the Team-Based Learning (TBL) Model with the Assistance of Phet Simulation on The Vibration Concept to Improve Learning Outcomes for Students - Juliatin P. Hali; Tirtawaty Abdjul; Ritin Uloli (Jurnal Penelitian Pendidikan IPA, 2023)
Strengthening the 2013 curriculum learning process is carried out through an approach known as a scientific approach that starts with observing, asking, trying, associating and communicating. Through learning activities using a scientific method, one of which is with the help of the Phet simulation, which is expected that students will be able to achieve graduate competency standards. In Team-Based Learning (TBL) learning, the activities carried out by students are mostly used for group activities, such as completing worksheets or tests given by the teacher. One of the assignments or tests is an experiment using a Phet simulation. The results of the activities carried out by the teacher can be used to create more structured groups. The device development model in this study uses the 4-D (four-D) model, which consists of (1) Define, (2) Design, (3) Development, and (4) Disseminate. Based on the results of the research and development of Team-Based Learning devices that have been carried out at SMP Negeri 2 Pulubala, several conclusions can be drawn: Through this research, science learning devices were produced that were valid, practical, and effective. The developed learning device is assessed by a construct validity test with a valid category with minor revisions/slight revisions to fulfil the eligibility validity as a learning device. Likewise, in terms of practicality, team-based learning-problem solving learning devices have met the level of suitability in terms of the implementation of learning and teacher and student response questionnaires. There was a significant change in the average score of students from pretest to posttest in individual and group tests after implementing Team-Based Learning devices. Using Phet simulations as learning media can facilitate the learning process in science learning